Primary cardiac tumor: a case report of right atrial angiosarcoma and review of the literature - Guo, Yujian; Liu, Qianzhen; Wu, Haibo (Frontiers in Oncology, 2023)
Primary cardiac angiosarcoma is a relatively rare tumor with early metastasis and poor prognosis. Radical resection of the primary tumor remains the primary approach for the optimal survival of patients with early-stage cardiac angiosarcoma without evidence of metastasis. This case involves a 76-year-old man with symptoms of chest tightness, fatigue, pericardial effusion, and arrhythmias who achieved good results after surgery to treat the angiosarcoma in the right atrium. In addition, literature analysis showed that surgery remains an effective way of treating primary early angiosarcoma.